2013
DOI: 10.1155/2013/502013
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Tree Segmentation in Medical Images Using Hessian-Based Multiscale Filtering and Level Set Method

Abstract: Vascular segmentation plays an important role in medical image analysis. A novel technique for the automatic extraction of vascular trees from 2D medical images is presented, which combines Hessian-based multiscale filtering and a modified level set method. In the proposed algorithm, the morphological top-hat transformation is firstly adopted to attenuate background. Then Hessian-based multiscale filtering is used to enhance vascular structures by combining Hessian matrix with Gaussian convolution to tune the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Table 2 specifies obtained values for the four metrics. From this table it could be observed that the introduced fuzzy algorithm achieves less MSE when compared to Jin manual method 4 and when compared with PSO algorithm presented in Ref. 5.…”
Section: Comparison Criteriamentioning
confidence: 92%
See 2 more Smart Citations
“…Table 2 specifies obtained values for the four metrics. From this table it could be observed that the introduced fuzzy algorithm achieves less MSE when compared to Jin manual method 4 and when compared with PSO algorithm presented in Ref. 5.…”
Section: Comparison Criteriamentioning
confidence: 92%
“…The proposed fuzzy-rule based algorithm results will be compared with two methods: manual Jin's algorithm 4 and the automatic PSO-based algorithm 5 .…”
Section: Comparison Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm locates the points of maximum curvature in the DEM which correspond to the surface trace of dykes. One common approach to analyze the curvature of elevation data is to use an eigenvalue analysis of the Hessian matrix [56,57]. The Hessian matrix is a 2 × 2 matrix composed of second-order partial derivatives of the input image, whereas the second-order partial derivatives are defined as a convolution with derivatives of Gaussian filter at scale σ.…”
Section: Extraction Of Structural Featuresmentioning
confidence: 99%
“…Hessian matrix (ℋ ఙ ‫,ܫ(‬ ‫))ݔ‬ is a second-order partial derivation which is a convolution of input image (I) at point ‫ݔ‬ and Gaussian (࣡ ఙ ) filter, as in Eq. 1 [8] [9]. ROI image is read in green channel and then the vessel tracking is applied, as in Fig.…”
Section: Vessel Trackingmentioning
confidence: 99%